2017
DOI: 10.14202/vetworld.2017.238-243
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of foot and mouth disease and peste des petits ruminants in sheep flock imported for immediate slaughter in Riyadh

Abstract: Aim:To detect and identify the causative agent or agents of the following clinical symptoms which were fever, lack of appetite, salivation, vesiculation, erosions of the buccal mucosa, nose, and feet. The signs vary from mild to severe. The mortality rate of the disease is high. The morbidity rate reaches up to 100%. Sheep also show bloody diarrhea and rapid respiration. Sheep flock resident in El-Kharje Governorate.Materials and Methods:A total of 50 serum samples and 50 buffy coat samples were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…The highest proportion of seropositivity could be attributed to the illegal introduction of animals from Sudan; thus, animals such as sheep and goats, if imported legally, must be put in quarantine before entering the country. Furthermore, many factors increase animal susceptibility to PPRV, including young age, low maternal immunity intake, poor nutritional status, and drastic climatic conditions [ 1 ]. Moreover, in a study [ 35 ] of 110 serum samples from ill, recovered, and apparently healthy animals that were tested for the presence of PPR antibodies by c-ELISA, 84 animals were positive for PPR antibodies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest proportion of seropositivity could be attributed to the illegal introduction of animals from Sudan; thus, animals such as sheep and goats, if imported legally, must be put in quarantine before entering the country. Furthermore, many factors increase animal susceptibility to PPRV, including young age, low maternal immunity intake, poor nutritional status, and drastic climatic conditions [ 1 ]. Moreover, in a study [ 35 ] of 110 serum samples from ill, recovered, and apparently healthy animals that were tested for the presence of PPR antibodies by c-ELISA, 84 animals were positive for PPR antibodies .…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that small ruminants, when kept in close contact with large ruminants, could serve as reservoirs of FMD virus and as potential sources of infection for susceptible livestock. Results of detection of FMDV and PPRV antibodies using the OD of the ID Vet c-ELISA Kit and the ID screen PPR Competition ELISA Kit, respectively, indicated that testing of 50 serum samples from the Marino sheep flock resulted in 38/50 (76%) and 32/50 (64%) positive for antibodies against FMDV and PPRV, respectively [ 1 ]. The study reflected the high susceptibility of the imported flock to infection with FMDV and PPRV, which are viruses that are endemic in the Kingdom of Saudi Arabia; as such, so the flocks imported for slaughter should be quarantined and vaccinated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High prevalence of antibodies in the examined animals may be due to their presence next to cows, which is the main reservoir of the BTV. Mixed breeding between different species of livestock is an obstacle in the control operations and a means of transmitting diseases between these species [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although various FMDV vaccines are available in most countries, ongoing outbreaks are still reported in some of these animal populations (Eble et al 2015). Also in Saudi Arabia, several FMDV outbreaks have been reported (Samuel et al 1988; Abd El-Rahim et al 2016; Mahmoud and Galbat 2017). One study during 1986–1987 reported the detection of serotype A in some animals from Saudi Arabia and Iran (Samuel et al 1988).…”
Section: Introductionmentioning
confidence: 99%